Il Museo di Storia Naturale dell'Università degli Studi di Firenze. Le collezioni antropologiche ed etnologiche / The Museum of Natural History of the University of Florence. The Anthropological and Ethnological Collections Le collezioni antropologiche ed etnologiche - Moggi Cecchi, Jacopo (Cataloghi e collezioni, 2014)
This volume is dedicated to the Anthropological and Ethnological section of the Natural History Museum. First the historical journey of the collections is traced from the antique nucleus of the Medici to the foundation of the National Museum of Anthropology and Ethnology, when Florence was the capitol of Italy, and the discipline of anthropology was born. The second part illustrates the multivariate collections from all over the globe. They are a precious record of the past and present biological and cultural diversity of our species opening wide horizons that rigorously connect science to the many faces of human culture, including art. The third section is dedicated to current research and opens new prospectives on the significance of ethnological and anthropological collections due to new technology and in light of a new appreciation of the museum as a living "zone of contact".